2017
DOI: 10.2147/ppa.s140457
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence has an impact on disease activity in rheumatoid arthritis: a systematic review and meta-analysis

Abstract: ObjectiveDisease activity of rheumatoid arthritis (RA) patients was often measured by the 28-joint count disease activity score (DAS-28), which consists of 28 swollen and tender joint counts, patient’s assessment of disease activity (visual analog scale [VAS]) and erythrocyte sedimentation rate. C-reactive protein was also used to measure disease activity in RA patients. The aim was to explore the impact of medication adherence on disease activity in patients with RA.MethodsA systematic search was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
(55 reference statements)
4
34
0
1
Order By: Relevance
“…Given the cross‐sectional nature of our evaluation of adherence at baseline, a causal relationship is difficult to prove. However, one could make the case that poor adherence might be responsible for higher levels of disease activity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the cross‐sectional nature of our evaluation of adherence at baseline, a causal relationship is difficult to prove. However, one could make the case that poor adherence might be responsible for higher levels of disease activity .…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed a correlation between the change in the CQR‐19 score and the change in HAQ score in the TM group, suggesting a modest clinical impact. In view of the well‐documented link between adherence and the effectiveness of MTX, the anticipated clinical impact would lead to a decrease in the DAS28 and, potentially, in cardiovascular mortality . Last, overall patient satisfaction was high, and even higher in patients with an additional intervention (the PC and TM groups).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 50% of women with OP discontinue prescribed treatment in 1 year (14). Nonadherence is associated with increased disease activity, long‐term joint damage in gout and RA, and increased fractures in OP (12,15–19).
Trust in the doctor and doctor’s knowledge, medication effectiveness and side effects, and patients’ medication‐taking routine and knowledge were factors important to patients and caregivers for medication adherence. Strengthening doctor–patient trust, balancing medication benefits and harms, and empowering patients with medication knowledge and skills to form effective routines are potential solutions for medication nonadherence that require further investigation.
…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated an association between higher medication adherence and better clinical response to therapies in RA patients [ 8 13 ]. Of these investigations, one has indicated that medication adherence is associated with improvements in disease activity and physical functional outcomes among DMARDs-naïve patients, but not among existing users [ 13 ].…”
Section: Introductionmentioning
confidence: 99%